2022
DOI: 10.1111/trf.16882
|View full text |Cite
|
Sign up to set email alerts
|

Digitally enabled hemovigilance allows real time response to transfusion reactions

Abstract: Background Transfusion carries a risk of transfusion reaction that is often underdiagnosed due to reliance on passive reporting. The study investigated the utility of digital methods to identify potential transfusion reactions, thus allowing real‐time intervention for affected patients. Method The hemovigilance unit monitored 3856 patients receiving 43,515 transfusions under the hemovigilance program. Retrospective comparison data included 298,498 transfusions. Transfusion medicine physicians designed and vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…It is thought that active surveillance can mitigate the problem of underreporting seen with passive surveillance. [14][15][16]94 This is why we elected to focus on active surveillance studies, while also analyzing passive surveillance to allow for comparison. Toy et al performed an active surveillance study at two centers where 10 cases of TRALI were identified out of 123,731 units transfused (8Á1/100,000) using donor risk mitigation practices during 2009.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is thought that active surveillance can mitigate the problem of underreporting seen with passive surveillance. [14][15][16]94 This is why we elected to focus on active surveillance studies, while also analyzing passive surveillance to allow for comparison. Toy et al performed an active surveillance study at two centers where 10 cases of TRALI were identified out of 123,731 units transfused (8Á1/100,000) using donor risk mitigation practices during 2009.…”
Section: Discussionmentioning
confidence: 99%
“…This could take the form of broader implementation of active surveillance; however, in practice, active surveillance can be highly resource intensive, which presents challenges outside of a research setting. [14][15][16]94 Use of novel data-driven approaches to active surveillance of electronic health records, such as large language models or other machine learning methods could facilitate enhanced detection. 100 In conclusion, we used meta-analysis to obtain estimates for TRALI rates for RBCs, platelets, and plasma, by component transfused.…”
Section: Discussionmentioning
confidence: 99%
“…15 In this issue of TRANSFUSION, Villamin et al take transfusion reaction surveillance to the next level. 16 They describe the roll-out of an active hemovigilance unit, which combines electronic vital sign change triggers with an action team available to respond to a possible transfusion reaction in real time. Using their EHR, they created a dashboard for tracking all transfusions as they are initiated for up to 6 h post-transfusion.…”
mentioning
confidence: 99%
“…For example, the ordering of diphenhydramine or furosemide while a transfusion is occurring may indicate other patient symptoms requiring relief. 16 A nurse may document the presence of flushing or back pain in a clinical note an hour after transfusion. The use of correlate data for adverse event identification is already being used.…”
mentioning
confidence: 99%
See 1 more Smart Citation